Working with social justice and marginalized groups in museums: How Intercultural museum in Oslo contributes to empower minority youths through its museum practice - Fossum, Mina Augestad (2021)
This small-scale case study explores how Intercultural museum (Interkulturelt museum, IKM) at Grønland in Oslo works to include and give young people a voice in their museum practice, and how this can contribute to impact upon issues of social justice. Considering museum’s increased focus on social justice world-wide, IKM provides a unique case of a museum actively pursuing a social justice agenda by engaging with marginalized groups in its local community. Empirically based on semi-structured interviews, this study explores how IKM worked with the grassroot initiative called Cooperation for Inclusive Dialogue (Samarbeid for Inkluderende Dialog, SID) by allowing it to produce its own exhibition at the museum. SID is a voluntary organization consisting of young men with minority background in their mid-20, that works to combat the feeling of alienation among minority youth in central Oslo, by facilitating for inclusive dialogue and highlighting youth voices. It especially targets youth from the culturally diverse neighborhoods of Grønland and Tøyen, that struggle with finding their way in life due to difficult socio-economic conditions. Drawing on museological and critical educational theories, the thesis especially analyses what methods, mechanisms, and approaches IKM used to include SID in its museum practice and how this affected the parties involved and the local community. Dealing with two marginalized groups at museums, the study contributes to shed light on how museums can engage with issues of social justice by collaborating with new groups in the museum. It offers an example of how a museum can connect to its younger visitor groups and contribute to empower marginalized groups in society through its museum practice. It also shows how museums can play an important role in creating more tolerant, respectful, and inclusive societies where everyone feels welcome and accepted.